CHECKLIST OF MICROALGAE COLLECTED FROM DIFFERENT HABITATS IN PENINSULAR MALAYSIA FOR SELECTION OF ALGAL BIOFUEL FEEDSTOCKS - Phang, Siew-Moi; Mustafa, Emienour Muzalina; Ambati, Ranga Rao; Nik Sulaiman, Nik Meriam; Lim, Phaik-Eem; Abdul Majid, Nazia; Dommange, Xavier; Schwob, Cyrille; Liew, Kan-Ern (Malaysian Journal of Science, 2015)
A survey of 30 collections sites in Peninsular Malaysia, representing five types of habitats, namely, hot springs, eutrophicated freshwater lake, palm oil mill effluent ponds, brackish and marine water habitats, yielded 79 environmental samples. The total number of algal taxa and genera identified were 73 and 52 respectively; with 9 genera and 11 taxa of Cyanophyta; 25 genera and 33 taxa of Bacillariophyta; 13 genera and 16 taxa of Chlorophyta and 5 genera and 13 taxa of Euglenophyta. In terms of cell numbers, the samples from the oil palm mills had the highest cell density. Of the isolates obtained from the samples collected, only six genera, namely the Cyanophyte Cyanosarcina, the Chlorophytes Chlorella, Chlamydomonas, Chlorococcum, Scenedesmus and the Euglenophyte Euglena, are discussed in terms of their growth and biochemical profiles in this paper. Chlorococcum and Euglena had the highest specific growth rate, Âµ, followed by Chlorella and Scenedesmus. Biomass productivity at day 12 was generally higher than that at day 8 for all genera. Highest biomass productivity was from Chlorella followed by Chlamydomonas. Highest lipid productivity was from Chlorella and Chlamydomonas on day 12. Chlorella had the highest carbohydrate productivity followed by Chlamydomonas. Chlorella and Chlamydomonas had the highest protein productivity. In this short survey, some interesting algae were identified and isolated, which proved to have potential for use as feedstocks for biofuel production. Keywords:microalgae, checklist, specific growth rate, carbohydrate, protein, lipid productivity